The Role of HR in Nurturing Organizational Innovation - Mahdia, Asrini (Management Studies and Business Journal (PRODUCTIVITY), 2024)
This research aims to investigate the role of Human Resources (HR) in supporting organizational innovation. Through systematic literature analysis, this research explores factors such as organizational culture, recruitment and selection processes, training and development, rewards and recognition, teamwork and collaboration, policies of flexibility and openness, communication and knowledge sharing, and the role of leaders in encouraging innovation . The findings of this research indicate that the integration of HR functions into an organization's innovation strategy, along with the implementation of innovation-oriented HR policies, can increase the overall level of organizational innovation. Although this research is faced with limitations in the range of literature selected, the research implications provide important insights for HR practitioners and organizational leaders in strengthening the innovative capacity of their organizations.